A multimodal approach to the voicing contrast in Turkish: Evidence from simultaneous measures of acoustics, intraoral pressure and tongue palatal contacts. (November 2018) - Ünal-Logacev, Özlem; Fuchs, Susanne; Lancia, Leonardo
Highlights: Acoustic, articulatory and aerodynamic data for the voicing contrast in Turkish. Negative VOT for the voiced alveolar plosives and positive VOT for the voiceless cognate. Linear relation between articulation and pressure for voiced stops and nonlinear relation for the voiceless cognates. Comparison of Generalized Additive Mixed Models (GAMMs) with single time point analysis. Abstract: The aims of the study are to investigate acoustic, aerodynamic and supralaryngeal properties of the voicing contrast in Turkish and to better understand the relation between these factors in the maintenance and inhibition of phonetic voicing. For this purpose, simultaneous recordings were carried out using electropalatography, a piezoresistive pressure transducer and a microphone for six speakers of Turkish. The voiced /d, dʒ/ and voiceless /t, tʃ/ target sounds occurred in word-initial position in intervocalic context. Single time points were selected to study the voicing contrast and its corresponding properties. The most pronounced differences between voiced and voiceless consonants were the relative voicing during closure and the velocity maximum of intraoral pressure (Pio). Phonologically voiced stops showed a relatively long voicing portion, a negative VOT (for /d/) and a slower rise in Pio. Voiceless stops were realized with less voicing, positive VOT (for /t/) and a steep intraoral pressure rise. However, differences were not found for tongue-palatal contact patterns at full closure. The analysis of mutual dependence between articulatory and aerodynamic measures through Generalized Additive Mixed Model (GAMM) showed a linear relation between the two measures in voiced stops and a nonlinear relation for the voiceless. These results are discussed in light of laryngeal-oral coordination and cavity enlargement. Moreover, the different methodological approaches and their benefits are considered.